Can Law Protect Local Identity? Comparing Indonesia and Oman on Geographical Indications in Global Trade - Waspiah Waspiah; Rodiyah Rodiyah; Asmarani Ramli; Souad Ahmed Ezzerouali; Valerio Sebastian (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2026)
Geographical Indications (GIs) serve as a vital form of communal intellectual property, safeguarding local identity, cultural heritage, and economic value. This study investigates the legal frameworks and enforcement mechanisms of GI protection in Indonesia and Oman within the context of global trade. Indonesia’s Law No. 20 of 2016 provides a robust framework, demonstrated by the success of Java Sindoro-Sumbing Coffee. Conversely, while Oman’s Royal Decree No. 40/2000 establishes a legal basis, practical implementation—particularly for agricultural products—remains hindered by nascent regulatory structures and low producer awareness. Utilizing a socio-legal approach, this research gathers data through interviews with local producer groups, government officials, and GI associations to identify gaps in dispute resolution and cross-border enforcement. The novelty of this study lies in its proposal of a hybrid legal model that integrates litigation and non-litigation strategies, adaptable for both mature and emerging GI jurisdictions. This research contributes to the field by enhancing legal awareness and providing a practical framework to ensure local identity is preserved and respected in the global marketplace.